Relationship between soluble neuropilin-1 in the gingival crevicular fluid of early pregnant women and different severities of periodontitis: A cross-sectional study - Diego Prieto; Karina Pino-Lagos; Ornella Realini; Felipe Cáceres; Ignacio Retamal; Alejandra Chaparro (Journal of Oral Biology and Craniofacial Research)
Background: Pregnancy exacerbates the periodontal inflammation; however, the biological mediators involved are not well characterized. Neuropilins (NRPs) are transmembrane glycoproteins involved in physiological and pathogenic processes such as angiogenesis and immunity but its relationship with periodontal disease in pregnant women has not been studied. Objective: To explore the soluble Neuropilin-1 (sNRP-1) levels in gingival crevicular fluid (GCF) samples during early pregnancy and its association with the periodontitis severity and periodontal clinical parameters. Methods: 80 pregnant women were recruited, and GCF samples were collected. Clinical data and periodontal clinical parameters were recorded. sNRP-1 expression was determined by ELISA assay. The relationship between sNRP-1(+) pregnant women with the severity of periodontitis and periodontal clinical parameters was determined by Kruskal-Wallis and Mann-Whitney tests. Spearman's test estimated the correlation between sNRP-1 levels and periodontal clinical parameters. Results: Periodontitis was classified as mild in 27.5% (n = 22) women, moderate in 42.5% (n = 34), and severe in 30% (n = 24). sNRP-1 expression was higher in the GCF of pregnant with severe (41.67%) and moderate (41.17%) periodontitis compared than in those with mild periodontitis (18.8%). The sNRP-1(+) pregnant had a higher BOP (76.5% v/s 57%; p = 0.0071) and PISA (1199.5 mm2 v/s 880.2 mm2; p = 0.0282) compared with sNRP-1(−). A positive correlation between sNRP-1 levels in GCF and BOP (p = 0.0081) and PISA (p = 0.0398) was observed. Conclusions: The results suggest that sNRP-1 could be involved in periodontal inflammation during pregnancy.